Adverse childhood experiences and delinquent behaviour: predictors and mediating variables - Martins, Joana (2021)
Adverse childhood experiences (ACEs) have been identified as a risk factor for the development of mental health and behavioural outcomes throughout life, including delinquent behaviours. This article focuses on the relationship between ACEs and delinquent behaviour (DB), seeking to identify predictors and mediating variables. Methods: The quantitative study comprised 175 Portuguese adolescents, aged 12 and 17 years of age (M = 14.99, SD = 2.26). Results: ACEs and exposure to traumatic events (ETE) are predictive of DB. Antisocial traits (AT) was found to be mediating the relationship between ACEs and DB, as well as the relation between ETE and DB. Conclusion: The results indicate that it is necessary that professionals in health behaviour field prevent and intervene in ACEs and in ETE, both predictors of DB. The results of this study allow to understand the role of ACEs in DB and its mediating variables, which must be considered to mitigate the harmful impact of ACEs in DB.